Phase field modeling of hydraulic fracturing with interfacial damage in highly heterogeneous fluid-saturated porous media. (December 2017) - Xia, L.; Yvonnet, J.; Ghabezloo, S.
Highlights: Extension of phase field to interface damage is extended to saturated porous media. The fluid can flow within both bulk cracks and interfacial cracks. The formulation is adapted to voxel-based models of realistic heterogeneous media. 3D simulations of hydraulic fracture with interfacial damage induced by the fluid. Abstract: In this work, we propose an extension of the phase field model for the modeling of hydraulic fracturing or cracking in heterogeneous saturated porous media. The involved extensions comprise: (a) taking into account interfacial damage between the inclusions and the matrix; (b) modeling fluid flow within both matrix cracks and interfacial cracks; (c) the possibility to handle geometries of the heterogeneous media in the form of regular grids of voxels e.g. as obtained from experimental imaging techniques. The developed numerical framework is based on the phase field method with a regularized description of both bulk and interface discontinuities, extended to a fully coupled hydro-mechanical framework. Both 2D and 3D examples are presented for hydro-mechanical microcracking initiation and propagation in voxel-based models of complex heterogeneous media with interfacial damage between the inclusions and the matrix.